2009
DOI: 10.1016/j.exphem.2009.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells suppress B-cell terminal differentiation

Abstract: Objective-Mesenchymal stem cells (MSCs) have been shown to possess immunomodulatory properties on a diverse array of immune cell lineages. However, their effect on B-lymphocytes has remained unclear. We investigated the effect of MSCs on B cell modulation with a special emphasis on gene regulation mediated by MSC humoral factors.Methods-MSCs were isolated from C57BL/6 bone marrow and expanded in culture. Splenic B cells were purified using anti-CD43 antibody and immunomagnetic beads. B cells and MSCs were co-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
236
2
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(258 citation statements)
references
References 45 publications
12
236
2
8
Order By: Relevance
“…This interpretation is consistent with the finding that MSC therapy does not interfere with virus-specific T cell responses [Karlsson et al, 2008]. Studies of the influence of MSC on B cell function have also generated heterogeneous results [Corcione et al, 2006;Rasmusson et al, 2007;Rafei et al, 2008;Traggiai et al, 2008;Asari et al, 2009]. Co-culture of human MSC with purified B cell populations under stimulatory conditions may inhibit B cell activation (proliferation differentiation, immunoglobulin (Ig) production and chemotaxis) [Corcione et al, 2006].…”
Section: Msc Suppression Of Adaptive Immunitysupporting
confidence: 74%
“…This interpretation is consistent with the finding that MSC therapy does not interfere with virus-specific T cell responses [Karlsson et al, 2008]. Studies of the influence of MSC on B cell function have also generated heterogeneous results [Corcione et al, 2006;Rasmusson et al, 2007;Rafei et al, 2008;Traggiai et al, 2008;Asari et al, 2009]. Co-culture of human MSC with purified B cell populations under stimulatory conditions may inhibit B cell activation (proliferation differentiation, immunoglobulin (Ig) production and chemotaxis) [Corcione et al, 2006].…”
Section: Msc Suppression Of Adaptive Immunitysupporting
confidence: 74%
“…In the present study, UC MSCs significantly depressed the serum concentration of IL-4 3 months after transplantation, which may have inhibited humoral immunity in the SLE patients and indirectly suppressed the secretion of autoantibodies, especially anti-dsDNA antibody (which is most closely correlated with clinical outcome in mice and humans with SLE [39]). In addition, it has been shown that MSCs exert a suppressive effect on B cell activation and terminal differentiation to plasma cells (40); therefore, suppression of humoral immunity may be one mechanism involved in the treatment effect of UC MSCT.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6, which is involved in the reversion of the maturation of dendritic cells to an immature phenotype, mediates MSC interference with the maturation of dendritic cells [50]. MSCs were found to inhibit B-cell proliferation by releasing soluble factors, especially B lymphocyte-induced maturation protein-1(Blimp-1), which is necessary for immunoglobulin production [72].…”
Section: Mscs and Target Cells: A Long-distance Relationshipmentioning
confidence: 99%